Implementation of Data Mining Algorithm C4.5 to Predict Loan Payments in the Harum Manis Women's Union in Sirnoboyo Village - Miftahul Mukti Anas (Fakultas Teknik Universitas Bhayangkara, 2024)
The women's union,